2017
DOI: 10.1371/journal.pone.0180226
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of active tuberculosis notification from 2005 to 2014 in Xinjiang, China

Abstract: ObjectivesXinjiang is one of the highest TB-burdened provinces of China. A time-series analysis was conducted to evaluate the trend, seasonality of active TB in Xinjiang, and explore the underlying mechanism of TB seasonality by comparing the seasonal variations of different subgroups.MethodsMonthly active TB cases from 2005 to 2014 in Xinjiang were analyzed by the X-12-ARIMA seasonal adjustment program. Seasonal amplitude (SA) was calculated and compared within the subgroups.ResultsA total of 277,300 confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 24 publications
12
48
1
Order By: Relevance
“…Contrary to a study published in India (12), which showed Northern areas to have greater seasonal variation than those in central southern regions, our study shows reduced seasonal variation in regions further from the equator. Our results are consistent with a study looking at the seasonality of TB in Xinjiang, in which greater seasonality was noted in southern Xinjiang (34ºN-42ºN) than eastern and northern regions (43ºN-48ºN); however, the difference was not statistically signi cant (9). In the USA, the amplitude of TB seasonality has not been shown to vary according to latitude (6).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Contrary to a study published in India (12), which showed Northern areas to have greater seasonal variation than those in central southern regions, our study shows reduced seasonal variation in regions further from the equator. Our results are consistent with a study looking at the seasonality of TB in Xinjiang, in which greater seasonality was noted in southern Xinjiang (34ºN-42ºN) than eastern and northern regions (43ºN-48ºN); however, the difference was not statistically signi cant (9). In the USA, the amplitude of TB seasonality has not been shown to vary according to latitude (6).…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study are consistent with those of a smaller study looking at the seasonality of TB in a single district, Lahore, Pakistan, in which the investigators showed a peak in pulmonary TB cases in the second quarter of the year (17). Several studies (6,9,12,22) have explored the relationship between distance from the equator and seasonal variation of TB, and it is plausible that the seasonality of TB is more pronounced in areas where UV exposure is reduced and dermal vitamin D synthesis is low (12,22).…”
Section: Discussionsupporting
confidence: 90%
“…The reason for the decrease in patients reported in February is that the Chinese Spring Festival usually falls in February, in which people are busy celebrating the lunar New Year, and avoiding to seek medical care. This seasonal pattern is the same as that of a national study [12,13], and studies in Guangxi province [36], Xinjiang Uygur Autonomous Region [37], Zhaotong city of Yunnan province [24,32] and other western regions, but a little different from that of studies in Zhejiang province [23] , Hong Kong [38] and Taiwan [39], which are located in the eastern coastal area.…”
Section: Discussionsupporting
confidence: 73%
“…A study showed that from 2004 to 2008, April was the peak month for student TB cases in China, followed by May and March [15]. The seasonality of active TB registration was peaked in March in Xinjiang, China [16]. There were also some studies on the seasonality and trend analysis of TB incidence around the world [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%